2014
DOI: 10.1007/s00223-013-9834-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tartrate-Resistant Acid Phosphatase Expression in Osteoblasts and Osteocytes in Experimental Osteoporosis in Rats

Abstract: Tartrate-resistant acid phosphatase (TRAP) is known as an osteoclast marker, but osteoblasts and osteocytes in the vicinity of bone remodeling sites also express TRAP. Cell culture studies suggest that osteoblasts endocytose osteoclastic TRAP for inactivation. To evaluate whether changes in osteoclast activity could alter TRAP expression in osteoblasts and/or osteocytes in vivo, we studied the ovariectomized and vitamin D-deficient rat (Ovx-D) and rats healing from rickets. Bone sections were analyzed for TRAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 38 publications
1
30
1
1
Order By: Relevance
“…Similarly, the serum CTX level is an important biomarker for bone resorption. Increased levels of TRAP and CTX were shown in OVX rats [Solberg et al, 2014]. A previous study showed that tea consumption in rats with OVX-induced bone loss can suppress the level of TRAP, one of the osteoclast-specific genes [Wu et al, 2018].…”
Section: Introductionmentioning
confidence: 87%
“…Similarly, the serum CTX level is an important biomarker for bone resorption. Increased levels of TRAP and CTX were shown in OVX rats [Solberg et al, 2014]. A previous study showed that tea consumption in rats with OVX-induced bone loss can suppress the level of TRAP, one of the osteoclast-specific genes [Wu et al, 2018].…”
Section: Introductionmentioning
confidence: 87%
“…TRAP has been implicated as a potential drug target because of its association with several pathologies, such as bone‐associated diseases, chronic inflammation, and cancer . Several attempts to find potent and specific inhibitors for TRAP have been performed; however, the compounds found are often toxic and lack drug‐like characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Oste ocy ty po sia da ją takie sa me en zy my hy dro li zu ją ce, jak oste okla sty i wy kazu ją eks pre sję wi nia no opor nej fos fa ta zy kwa śnej (TRAP, ang. Tar tra te -re si stant acid pho spha ta se), en zymu uzna wa ne go za spe cy ficz ny dla oste okla stów [34,35]. In ni au to rzy jed nak nie wy ka za li eks pre sji ge nów dla wi nia no opor nej kwa śnej fos fa ta zy w oste ocy tach ko ści szczu rów pod da nej ob cią że niu [36].…”
Section: Osteocyte Bone Resorption (Osteocytic Osteolysis)unclassified
“…Do nie daw na je dy ną do stęp ną usta lo ną li nią mysich ko mó rek o ce chach oste ocy tów by ła my sia li nia bra nes of osteocytes and their processes provide a large surface for ion exchange between bone matrix and the fluid which fills lacunae and canaliculi. Osteocytes are armed with the same hydrolytic enzymes as are osteoclasts, and express tartrate-resistant acid phosphatase, an enzyme considered specific for osteo clasts [34,35]. Some authors, however, were una ble to detect this enzyme in osteocytes from bone subjected to mechanical loading [36].…”
Section: Ho Dow Le Oste Ocy Tów In VI Tromentioning
confidence: 99%